Bahasa Inggris - Soenarno, M. S.; Emilliana, P. A.; Arifin, M. (Universitas Bengkulu, 2024)
Tallow is a by-product of the meat processing industry. Tallow is commonly used as a raw material in soap making. This studi aims to evaluate the antibacterial activity of tallow-based soap with varying amounts of tea tree and peppermint extracts. This study used a completely randomized design with the addition of tea tree and peppermint extracts 0% (P1), addition 2% (P2), addition 5% (P3), addition 8% (P4). The parameters of this study were water content, pH, free fatty acids, and antibacterial activity tests against Escherichia coli, Staphylococcus aureus, and Propionibacterium acnes. The results showed that tea tree and peppermint extracts had no significant effect on the water content, pH and free fatty acid values. Meanwhile, the results of antibacterial activity showed significantly different results (P<0.05) for E. coli and S. aureus but were not significant for P. acnes. Adding tea tree and peppermint extracts to tallow-based soap can enhance its antibacterial properties without affecting the physical quality of the soap.